Large oral focal mucinosis: a case report - Karla Rovaris da Silva; Bárbara Vanessa de Brito Monteiro; Thayse Silva Aragão Norões; Gustavo Pina Godoy; Márcia Cristina da Costa Miguel (Sociedade Brasileira de Patologia Clínica, 2014)
The aim of this article is to report the case of a 23-year-old female patient that sought dental service for examination of an asymptomatic slow-growing large lump in the mandibular gingiva causing displacement of the right first molar. Excisional biopsy, histopathological analysis, Alcian blue/periodic acid-Schiff (PAS) staining and immunohistochemistry analysis for S-100 were performed. The diagnosis established was oral focal mucinosis. After three years, the patient is still under follow-up, without any recurrences. Although cases of oral focal mucinosis of this particular size are rare, this entity should be considered in the differential diagnosis of oral lesions located in the gingiva.